The Socioeconomic Impacts of COVID-19 on Households in Cambodia, Report No. 2 : Results from the High-Frequency Phone Survey of Households, Round 2 - Karamba, Wendy; Tong, Kimsun (World Bank, Washington, DC, 2021)
This brief summarizes the findings of round 2 (R2) of the high-frequency phone survey (HFPS) of households. The information presented is based on a sample of 1,667 households, of which 612 were drawn from the nationally representative living standard measurement study plus (LSMS+) and 1,055 from the list of beneficiaries of the conditional cash transfer program for pregnant women and children under 2 with an IDPoor equity card (IDPoor sample). IDPoor is Cambodia’s national poverty identification program and official targeting mechanism for programs that support the poor. Unless otherwise noted, the results presented are primarily drawn from the LSMS sample. The results of R2 implemented August to September 2020 are compared against results of round 1 (R1) implemented May to June 2020 to trace the evolution of key indicators. The same households will be tracked over 10 months, with selected respondents - typically the household head - completing interviews every 8 weeks. Monitoring the well-being of households over time will improve understanding of the effects of, and household responses to the coronavirus disease 2019 (COVID-19) pandemic in near-real time.